a) If "p_1 (x) \\in P^{(e)}" and "p_2 (x) \\in P^{(e)}" and if "\\alpha, \\beta \\in \\R", then
"p (x) \\equiv \\alpha p_1 (x) + \\beta p_2 (x) = \\alpha p_1 (- x) + \\beta p_2 (- x) = p (-x) ,"so that "p (x) \\in P^{(e)}". Similarly, if "p_1 (x) \\in P^{(o)}" and "p_2 (x) \\in P^{(o)}", then
"p (x) \\equiv \\alpha p_1 (x) + \\beta p_2 (x) \\\\ {} = - \\alpha p_1 (- x) - \\beta p_2 (- x) = - p (-x) \\, ,"so that "p (x) \\in P^{(o)}". This means that "P^{(e)}" and "P^{(o)}" are linear subspaces of "\\R [x]".
b) Let "p (x) = \\sum_i a_i x^i \\in P^{(e)}". Then "p(x) = p(-x)", so that
"\\sum_i a_i x^i = p(x) = \\frac12 \\left[ p(x) + p (-x) \\right] \\\\ {} = \\frac12 \\left[ \\sum_i a_i x^i + \\sum_i a_i (- 1)^i x^i \\right] \\\\ {} = \\frac12 \\sum_i a_i \\left[ 1 + (-1)^i \\right] x^i \\, ."Equating the coefficients on the left-hand side and on the right-hand side, we have
"a_i = \\frac12 a_i \\left[ 1 + (-1)^i \\right] \\, ,"placing no restriction on "a_i" if "i" is even, and implying "a_i = 0" if "i" is odd. Hence,
"P^{(e)} = \\left\\{ \\sum_i a_i x^i \\in \\R [x] \\, , a_i = 0 ~ \\text{if}~ i ~ \\text{is odd} \\right\\} \\, ."Let "p (x) = \\sum_i a_i x^i \\in P^{(o)}". Then "p (x) = - p (-x)", so that
"\\sum_i a_i x^i = p(x) = \\frac12 \\left[ p(x) - p (-x) \\right] \\\\ {} = \\frac12 \\left[ \\sum_i a_i x^i - \\sum_i a_i (- 1)^i x^i \\right] \\\\ {} = \\frac12 \\sum_i a_i \\left[ 1 - (-1)^i \\right] x^i \\, ."Equating the coefficients on the left-hand side and on the right-hand side, we have
"a_i = \\frac12 a_i \\left[ 1 - (-1)^i \\right] \\, ,"placing no restriction on "a_i" if "i" is odd, and implying "a_i = 0" if "i" is even. Hence,
"P^{(o)} = \\left\\{ \\sum_i a_i x^i \\in \\R [x] \\, , a_i = 0 ~ \\text{if}~ i ~ \\text{is even} \\right\\} \\, ."The space "P^{(e)} \\cap P^{(o)}" consists of "p (x) = \\sum_i a_i x^i \\in \\R[x]" such that "a_i = 0" for "i" both odd and even, hence, for all "i". Thus, "P^{(e)} \\cap P^{(o)} = \\{ 0 \\}".
c) We have "q (x) = p (x) + p (-x) = p (-x) + p(x) = q (-x) \\in P^{(e)}" for every "p (x) \\in \\R [x]".
If "p_1 (x), p_2 (x) \\in \\R [x]" and "\\alpha , \\beta \\in \\R", then
"\\psi \\left( \\alpha p_1 (x) + \\beta p_2 (x) \\right) \\\\ {} = \\frac12 \\left( \\alpha p_1 (x) + \\beta p_2 (x) + \\alpha p_1 (-x) + \\beta p_2 (-x) \\right) \\\\ {} = \\frac12 \\left( \\alpha p_1 (x) + \\alpha p_1 (-x) \\right) + \\frac12 \\left( \\beta p_2 (x) + \\beta p_2 (-x) \\right) \\\\ {} = \\alpha \\frac12 \\left( p_1 (x) + p_1 (-x) \\right) + \\beta \\frac12 \\left( p_2 (x) + p_2 (-x) \\right) \\\\ {} = \\alpha \\psi \\left( p_1 (x) \\right) + \\beta \\psi \\left( p_2 (x) \\right) \\, ."This demonstrates that "\\psi \\left( p (x) \\right)" is a linear map.
Further, we have
"\\psi^2 \\left( p(x) \\right) = \\psi \\left( \\frac12 \\left( p(x) + p(-x) \\right) \\right) \\\\ {} = \\frac12 \\left( \\frac12 \\left( p(x) + p(-x) \\right) + \\frac12 \\left( p(-x) + p(x) \\right) \\right) \\\\ {} = \\frac12 \\left( p(x) + p(-x) \\right) = \\psi \\left( p(x) \\right) \\, ."Thus, "\\psi^2 = \\psi".
The kernel of "\\psi" is the subspace formed by "p (x) \\in \\R[x]" such that "\\psi \\left( p (x) \\right) = 0." The last condition is equivalent to "p (x) + p (-x) = 0", or "p (-x) = - p (x)". Hence, the kernel of "\\psi" is the subspace "P^{(o)}", "{\\rm ker}\\, \\psi = P^{(o)}".
Comments
Leave a comment